PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X7 SMA NEGERI 2 SIAK HULU - Roslinda Wati Wati; Sakur '; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This reseacrh based on the students math ability class X7 of SMAN 21 Siak Hulu under Minimum Mastery Criteria with a percentage of 19,44% and the learning process still teacher center. The research was classroom action research. This research aims to outcomes students by implementing cooperative learning model structural approach of Numbered Heads Together. The subject of the research is students of class X7 of SMAN 21 Siak Hulu in the second semester academic years 2013/2014. There are 36 students in the class, consisting 20 girls and 16 boys. The instrument of data collection on this research are observation sheets and math achievement tests. The observation sheets are analyze in qualitative descriptive way, while the math achievement tests are analyze in quantitative descriptive way. The qualitative analysis showed an improvement of learning process prior to the action of the first cycle to the second cycle. Then the result of this research showed an increase in students from the base score with the percentage 19,44% to 63,9% on the first daily test and 72,2% on the second daily test. From the results of this study concluded that Cooperative Learning model structural approach of Numbered Heads Together can improve the math achievement of students at class X7 of SMAN 21 Siak Hulu in the second semester academic years 2013/2014. Key Word : Mathematics Learning Outcome, Cooperative Learning Model Structural Approach of Numbered Heads Together, Class Action Research